1867 Ill. Laws 650 - (:unkn) unknown (My University, 1867)
Authorized the town of Bloomington to regulate or prohibit the carrying or wearing of any pistol, colt, slung-shot, or cross knuckles, knuckles of brass, or other metal, Bowie-knife, dirk-knife, dirk, dagger or other dangerous or deadly weapon. Also provides for confiscation of such weapons.
Keywords: CARRY